2022
DOI: 10.3389/fimmu.2022.897835
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Related Genes Are Involved in the Progression and Prognosis of Asthma and Regulate the Immune Microenvironment

Abstract: BackgroundAutophagy has been proven to play an important role in the pathogenesis of asthma and the regulation of the airway epithelial immune microenvironment. However, a systematic analysis of the clinical importance of autophagy-related genes (ARGs) regulating the immune microenvironment in patients with asthma remains lacking.MethodsClustering based on the k-means unsupervised clustering method was performed to identify autophagy-related subtypes in asthma. ARG-related diagnostic markers in low-autophagy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The relationship between immune cells and hub genes is also the focus of existing research 53 . Asthma is a chronic airway inflammatory disease involving multiple cellular components, and several immune cells are involved in its pathogenesis 54 . In patients with PCOS, monocytes show significantly more infiltration and increased ability to secrete multiple cytokines, including potent proinflammatory cytokines, such as interleukin 1β 55 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between immune cells and hub genes is also the focus of existing research 53 . Asthma is a chronic airway inflammatory disease involving multiple cellular components, and several immune cells are involved in its pathogenesis 54 . In patients with PCOS, monocytes show significantly more infiltration and increased ability to secrete multiple cytokines, including potent proinflammatory cytokines, such as interleukin 1β 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Allergen-activated Th2 cells release cytokines, promoting airway eosinophil inflammation, airway hyperresponsiveness, and airway remodeling, which play a central role in the development of asthma [ 9 , 21 ]. Notably, ATG5 participates in the pathogenesis of asthma by mediating the differentiation of CD4 + T cells [ 12 , 22 ], which suggests that it may have a potential relationship with Th1 and Th2 cells in asthma patients. Our study revealed that in adult asthma patients, ATG5 was positively related to the Th2/Th1 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the expression of immune cells and immune functions in low- and high-risk groups, we further conducted using the R package “GSVA” ( 16 ). The composition of 22 tumors associated with immune infiltrate cells was investigated by the R package “CIBERSORT” in risk groups.…”
Section: Methodsmentioning
confidence: 99%